Patterns of Drug-Related Mortality in Maine, 1997-2002 - Sorg, Marcella; Greenwald, Margaret (Maine Policy Review, 2003)
Since 1997, the number and rate of drug-related deaths in Maine have risen dramatically. Contrary to what much of recent popular media coverage suggests, prescription medications and not illicit drugs are involved in the majority of these deaths, and many of these prescription medications are used by people from all walks of life. In this article, Sorg and Greenwald summarize the results of a recent statewide study to determine the characteristics of those in Maine who have died from drug-related causes over the past five years. They find that Maine’s substance abuse problem continues to be largely one of alcohol abuse. Further, they find that drug deaths and, by implication, substance abuse problems are found in all areas of the state, both rural and urban.
Keywords: Maine; substance abuse; drug-related mortality